EFFECT OF Musa acuminate AND Ocimum basilicum MIXED EXTRACTS ON BIOACTIVE RESIN’S FLUORIDE RELEASE - Kurnia Fatwati; Dewi Puspitasari; Maharani Laillyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Bioactive composite resin was materials that are able to released fluoride when the intra oral pH value drops. Mouthwash is one of the triggers for changes in pH of the oral cavity. The many side effects caused by chemical mouthwashes make herbal plants an alternative to natural mouthwash. Traditional plants that have the potential to be used as mouthwash include of Mauli Banana (Musa acuminata) and basil (Ocimum basilicum L.).Objective: To analyze the effect of Mauli banana stem (Musa acuminate) and basil leaves (Ocimum basilicum) mixed extracts on fluoride (F) release from bioactive resin. Method: Thirty specimens (15mm diameter x 1mm thick; n=5/group) were fabricated using Activa ™ Bioactive Restorative (Pulpdent). Mauli banana stem and basil leaves extracts mixture at the concentration of 25%, 50%, 75%, and 100% were respectively exerted as treatment groups while 0.2% Chlorhexidine Gluconate (CHX) and aquadest employed as control groups. Bioactive resin immersion was performed for 7 days in 37oC incubator prior to the measurement of F release using pH meter Lutron (208) TL Lutron (Taiwan). Results: One Way Anova and Post Hoc Dunnets-T3 not only depicted the significant differences among treatment groupprior tontly easurement ofrable bioactive resin durability in the oral cavity. on f of 50% (3.22±0.46ppm), 75% (2.31±0,45ppm), 100% (2.29±0.46ppm), but also control group CHX (2.31±0,45ppm), and aquadest (1.85±0.91ppm) compared to 25% treatment group (6.00±0.87ppm).Conclusion: There is a significant effect of Mauli Banana stem and basil leaves extract mixture on bioactive resin F release. Increasing concentration may reduce the number of F release yet achieve a preferable bioactive resin durability in the oral cavity.